Linear ubiquitination in immune and neurodegenerative diseases, and beyond. (29th April 2022) - Tokunaga, Fuminori; Ikeda, Fumiyo
Abstract : Ubiquitin regulates numerous aspects of biology via a complex ubiquitin code. The linear ubiquitin chain is an atypical code that forms a unique structure, with the C-terminal tail of the distal ubiquitin linked to the N-terminal Met1 of the proximal ubiquitin. Thus far, LUBAC is the only known ubiquitin ligase complex that specifically generates linear ubiquitin chains. LUBAC-induced linear ubiquitin chains regulate inflammatory responses, cell death and immunity. Genetically modified mouse models and cellular assays have revealed that LUBAC is also involved in embryonic development in mice. LUBAC dysfunction is associated with autoimmune diseases, myopathy, and neurodegenerative diseases in humans, but the underlying mechanisms are poorly understood. In this review, we focus on the roles of linear ubiquitin chains and LUBAC in immune and neurodegenerative diseases. We further discuss LUBAC inhibitors and their potential as therapeutics for these diseases.